Performance Evaluation of Kashan Industry Occupational Health Experts by Analytical Hierarchy Process in 2019 (Shahid Sadoughi University of Medical Sciences, 2020)
Abstract: Introduction: Appropriate performance of the occupational health experts working in industries can reduce occupational accidents and diseases. This study was conducted to evaluate the performance of  Kashan   industries occupational health experts to identify their weaknesses and strengths. Methods: This descriptive-analytical study was carried out on 60 occupational health experts in Kashan in 2019. The Ministry of Health checklist was used after applying the weight and calculating the incompatibility rate using the Analytic Hierarchy Process (AHP) method. Data were analyzed by SPSS 21 software. Results: Performance evaluation of the occupational health experts with the checklist indicated that the best performance was related to the public activity item, while the poorest performance was related to the occupational health item. The average score of total occupational health experts was 73.76. The results of linear regression analysis showed that the total  score of industrial health experts had a significant relationship with their work experience, education, and employment status (P <0.05).  Conclusion: In this study, we evaluated and prioritized48 sub- items related to the performance of industries' occupational health experts in Kashan. The findings suggested officials to consider these priorities in health interventions.